Lower Prevalence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection Among People Experiencing Homelessness Tested in Outdoor Encampments Compared With Overnight Shelters: Denver, Colorado, June–July 2020. (18th January 2022) - Rowan, Sarah E; McCormick, David W; Wendel, Karen A; Scott, Tracy; Chavez-van de Hey, Jesse; Wilcox, Kay; Stella, Sarah A; Kamis, Kevin; Burman, William J; Marx, Grace E
Abstract: Background: A better understanding of the risk for coronavirus disease 2019 (COVID-19) that people experiencing homelessness (PEH) face in congregate shelters versus unsheltered encampments is critical for an effective pandemic response. Methods: We analyzed factors associated with current and past severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among PEH in day and overnight shelters and encampments in Denver, Colorado, during June 2–July 28, 2020, and constructed multivariable logistic regression models to examine risk factors for SARS-CoV-2 RNA and seropositivity with age, race/ethnicity, testing location, testing month, and symptom status as predictor variables. Results: A total of 823 participants were tested for SARS-CoV-2 RNA, and 276 individuals were tested for SARS-CoV-2 antibodies. A greater percentage of PEH at overnight shelters tested positive for SARS-CoV-2 RNA (8.6% vs 2.5%, P  < .01) and antibodies (21.5% vs 8.7%, P  = .03) compared with encampments. In regression models, testing at an overnight shelter compared with testing at encampments (odds ratio [OR] = 3.03, 95% confidence interval [CI]: 1.16–9.02) had increased odds of a positive SARS-CoV-2 RNA result. Age >60 years compared with age <40 years (OR = 5.92; 95% CI: 1.83–20.3), Hispanic ethnicity (OR = 3.43; 95% CI: 1.36–8.95), and non-Hispanic Black race compared with non-Hispanic White race (OR = 3.07; 95% CI: 1.16–8.26), and testing at an overnight shelter compared to testing at encampments (OR = 2.45; 95% CI: 1.04–6.17) had increased odds of a positive antibody result. Conclusions: Our findings support the need for continuing assessment of mitigation strategies in shelters, increasing access to individual rooms and linkage to housing options for PEH, and supporting people to remain in encampments when these options are not available. Abstract : In the early months of the coronavirus disease 2019 pandemic, a greater proportion of persons experiencing homelessness tested positive for severe acute respiratory syndrome coronavirus 2 RNA and antibodies in overnight shelters compared with outdoor encampments in Denver, Colorado. Results remained significant when controlling for participants' characteristics.